The possibilities presented by educational technology for educational renewal in South Africa - Marais, De la Rey (Koers, 1992)
With the reality of large-scale political reforms in South Africa and the concomitant restructuring of educational policy in order to ensure equitable quality education for all South Africans, unprecedented creativity is required of everybody. In South Africa hopes are pinned on the possibilities offered by high-technology education media as a possible solution for many of the problems besetting the system. The article focuses on the possibilities an d limitations of educational media in the unique educational circumstances in South Africa. As a result of the reigning didactic circumstances in the country it is concluded that it is not necessarily the case that high-technology instructional media will resolve the educational difficulties of South-Africa.